DIAGNOSTIC VALUE OF NEUTROPHIL-LYMPHOCYTE RATIO TO DIFFERENTIATE ISCHEMIC AND HEMORRHAGIC STROKE - Martina Rentauli; Liong Boy Kurniawan; Darwati Muhadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Stroke is a neurologic emergency disease and the main cause of high mortality. The inflammatory process in stroke due to cell and tissue damage causes an increase of leucocyte prominently neutrophil. Neutrophil Lymphocyte Ratio (NLR) is an easy-to-measure inflammatory marker. There is only a few data of NLR in Indonesia. This study aimed to know the difference in NLR values among ischemic and hemorrhagic stroke and to find out the diagnostic NLR to differentiate ischemic and hemorrhagic stroke patients. This study was a retrospective cross-sectional study using secondary data from Medical Record of Wahidin Sudirohusodo Hospital, Makassar. Leucocyte, neutrophil, and lymphocyte first data from adult stroke diagnosed patients were taken. Data statistically analyzed and diagnostic value of NLR was determined by Receiver Operating Curve (ROC) analysis. Total of 402 patients was enrolled, 214 (54.72%) with ischemic stroke and 182 (46.8) with hemorrhagic stroke. There was a significant NLR difference between ischemic stroke (median 7.23) and hemorrhagic stroke (median 3.65) (p<0.001). Using cut-off 5.18, ROC curve showed of (AUC) 0.730 which had a weak performance to differentiate ischemic and hemorrhagic stroke with sensitivity 67.8% and specificity 68.6%. The neutrophil-lymphocyte ratio in hemorrhagic stroke is higher than ischemic stroke. Further studies with larger and more evenly distributed samples and consideration of sampling time are a suggestion.